Rural real estate tax in the state of São Paulo - Brazil: Fiscal renunciation and evasion - De Souza, José Gilberto [UNESP]; Gebara, José Jorge [UNESP] (My University, 2012)
This study analyzes the profile of collecting ITR - Rural Real Estate Tax - in the State of São Paulo between 1995 and 1997 and verifies the impact of the Laws 8817/94 and 9393/96, especially the latter when the Internal Revenue Service (SRF) declined the arbitration of the VTNm - minimum Bare Land Value - thus greatly reducing the rates of tax collection. Moreover, this study highlights the aspects of taxation in areas of land conflict where the bare land values often do not reflect the true market values of the land, mainly in the Western part of the State.© 2012 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Agricultural reform; Fiscal political affairs; Land prices; Rural real estate taxation